Exploring The Nexus: Pathological Narcissism, Substance Abuse, and Self-Regulation as Predictors of Suicidal Ideation in College Students - Akanbi, Samuel Toyin (Psikoislamika : Jurnal Psikologi dan Psikologi Islam, 2024)
The study explored the predictors of suicidal ideation among university undergraduates focusing on the roles of narcissism, substance usage, and self-regulation. A correlational approach was adopted for the study. A total of 1,411 undergraduates selected through a multistage random sampling from three Nigerian universities participated in the study. Suicide Ideation Scale (α= .76), The Short Self-Regulation Questionnaire (α=.87), Drug Abuse Screening Test (α=.7), and Pathological Narcissism Inventory (α=.94) were used to gather information from the participants. Data collected were subjected to statistical screening through the Pearson Product Moment Correlation and multiple regression. The outcomes showed that a combination of the three main predictors explained a total of 32% (R2=.322; F(4,1406)= 166.557; p